GENETIC ASSESSMENT OF CHLOROPHYLL A AND B, CAROTENOIDS AND STOMATAL CONDUCTANCE IN LEAF TISSUE OF UPLAND COTTON IN WATER STRESS CONDITIONS - A. Rehman; M. T. Azhar; 2 (Journal of Animal and Plant Sciences, 2020)
Water stress is a major threat to crop production in climate change scenario. Leaf physiological traits play an important role in maintenance of plant physiological processes under water stress. Therefore, the present study was conducted to characterize the leaf physiological traits of cotton under water stress as well as investigate the genetics of their inheritance. Sixty cotton hybrids along with parents were sown in field conditions in triplicate following split plot design under normal and water stress conditions. Data were collected for leaf physiological traits i.e. Chlorophyll a and b, carotenoids, stomatal conductance and transpiration rate. Crosses namely, CIM-482 × NIAB Karishma, MNH-93 × S-12, CRIS-134 × ACALA-1517-C, CP-15/2 × FH-1000 and CRIS-134 × CIM-506 exhibited higher estimates of heritability, heterosis and heterobeltiosis suggested the presence of potential for genetic improvement through breeding and selection. Analysis of variance revealed the presence of significant differences among the genotypes for all the studied traits. Beside the lines i.e. FH-900, MNH-93 and NIAB-111 and testers CIM-506, NIAB Karishma and MNH-129 were found to be good general combiner under water stress conditions. The preponderance of non-additive gene action for the traits mentioned in this manuscript depict that superior combinations in current study can be used in drought tolerant cotton varieties with early generation selection.
Keywords: Chlorophyll contents; Cotton; Genetic analysis; Stomatal conductance